The main environmental impacts of a university restaurant and the search for solutions - Rizk, M. C. [UNESP]; Nascimento, D. B. [UNESP]; Perão, B. A. [UNESP]; Camacho, F. P. (Taylor & Francis, 2018)
The objective of this study was to evaluate the food and water waste in a university restaurant. During the evaluated period, 18,083.08 kg of food were produced of which 17.85% had become solid waste that was disposed in the environment, being that US$ 1,079.65 of what was invested for production was lost. The consumption of water for the production of meals was 29.71 L, above the recommended level, contributes to a reduction of this natural resource, besides generating an additional amount of wastewater, increasing the volume of effluents dumped in the rivers. Thus, it is evident the need to develop actions aimed at optimizing the management of natural resources, reducing the waste and, consequently, the negative impacts caused by the restaurant’s activities. So, in order to minimize the impacts, environmental programs were designed to incorporate the principles of 4R (reduce, reuse, recycle and re-think).